2017
DOI: 10.18203/2320-6012.ijrms20171254
|View full text |Cite
|
Sign up to set email alerts
|

Role of high resolution sonography and color Doppler flow imaging in the evaluation of scrotal pathology

Abstract: Background: Scrotal swelling and pain are frequently encountered in clinical practice. Although to reach a diagnosis in some patients, history and physical examination are adequate, yet in a large percentage of patients, some additional studies are essential for complete evaluation of their symptoms. The clinical examination is often misleading or non-specific. The study shows the application of Gray-scale sonography, Color Doppler flow imaging (CDFI) and Power Doppler (PD) in the diagnosis of swelling, malpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…As regards inflammatory lesions, the sensitivity and specificity of grayscale and color Doppler ultrasound were 100% and 98.3%, respectively. Our findings are similar to several previous studies (12–17) that reported higher diagnostic accuracy of color Doppler ultrasound for the diagnosis of testicular pathologies. Sidhu et al.…”
Section: Discussionsupporting
confidence: 93%
“…As regards inflammatory lesions, the sensitivity and specificity of grayscale and color Doppler ultrasound were 100% and 98.3%, respectively. Our findings are similar to several previous studies (12–17) that reported higher diagnostic accuracy of color Doppler ultrasound for the diagnosis of testicular pathologies. Sidhu et al.…”
Section: Discussionsupporting
confidence: 93%
“…In human medicine, pulsed-wave Doppler, colour, and power Doppler are routinely applied to asses andrology status [ 56 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] and to determine the aetiology of dyspermia [ 23 , 77 ], demonstrating that sperm quality and quantity are dependent on tissue perfusion [ 23 , 26 , 78 , 79 , 80 ] and suggesting that the evaluation of testicular blood flow can predict the testicular function and, in turn, spermatogenesis [ 23 , 78 , 79 , 80 ].…”
Section: Colour Doppler and Power Dopplermentioning
confidence: 99%
“…Colour and power Doppler investigation shows testicular perfusion and detects abnormal flow patterns around neoplastic lesions. Several recent studies in men suggest the usefulness of colour and power Doppler ultrasonography in the evaluation of scrotal disorders, such as inflammatory conditions, torsion, neoplasm, cyst, and necrosis (Bertolotto et al, ; Gupta, Shrinuvasan, Srikanth, & Chidambaram, ). The aim of this study was to assess if colour Doppler ultrasound is a good tool for the investigation of testicular lesions in dogs, to report the sonographic features of the lesions and to measure colour and power Doppler parameters such as resistive index (RI), pulsatility index (PI), hypovascularization and hypervascularization analysing specific criteria, determining if they can be used to distinguish testicular neoplasms from the wide spectrum of non‐neoplastic pathological findings.…”
Section: Introductionmentioning
confidence: 99%